Hepatitis C viral dynamics during ribavirin priming differ according to prior treatment response and HCV type. Issue 11 (26th June 2016) - Fülöp, B.; Mihm, U.; Rohde, P.; Buggisch, P.; Schlosser, B.; Biermer, M.; Brodzinski, A.; Fischer, J.; Böhm, S.; van Bömmel, F.; Sarrazin, C.; Berg, T.
Summary: The mode of action of ribavirin is not completely understood. Ribavirin monotherapy has a measurable antiviral effect, which shows great variability. It might lead to an earlier steady state of plasma concentration and therefore enhance the effect of following combination treatment. The aim of this study was to evaluate the antiviral effect of ribavirin priming and its influence on sustained virologic response after combination treatment in a group of patients with different hepatitis C virus (HCV) types with or without prior treatment experience. Retrospective analysis of 75 patients (37 treatment naïve, 20 prior relapse, 16 prior nonresponse, genotype 1 present in 60 patients) from five centres who received ribavirin priming as part of an individual strategy in order to improve treatment outcome. All patients received ribavirin monotherapy with a mean dose of 14.5 mg kg −1 body weight for a mean of 28 days. After ribavirin priming, dual combination treatment with pegylated interferon alfa and ribavirin was started. The mean HCV RNA decline after ribavirin priming was 0.6 log10  IU mL −1 ( P <.001). The initial viral decline depended on HCV type and previous treatment status being highest among prior relapsers (0.8 log10  IU mL −1 ; P =.002) and HCV type 2/3 (1.2 log10  IU mL −1 ; P =.05) and lowest among those with prior nonresponse (0.3 log10  IU mL −1, P =.01). IFNL4 (formerly IL28B ) genotype for rs12979860 and IFNL3 genotype rs8099917 did not influence the initial viral decline. The study demonstrates a significant variability in the viral dynamics and antiviral efficacy of ribavirin monotherapy, which is mainly influenced by prior treatment status. The fact that the lowest response pattern was observed in prior nonresponder patients to pegylated interferon alfa plus ribavirin combination therapy can be taken as a hint that not only the individual interferon, but also the ribavirin sensitivity contributes significantly to the nonresponsive state.